STRATEGI LAYANAN BIMBINGAN DAN KONSELING BAGI SISWA TUNANETRA MTs YAKETUNIS YOGYAKARTA - Aisyah, Umi (Universitas Hamzanwadi, 2014)
MTs Yaketunis Yogyakarta is a formal educational institution that organizes guidance and counseling services. Becomes interesting when all students are blind people and teacher guidance and counseling are also blind people. This study aims to determine strategies strategy guidance and counseling services to be performed for blind students in MTs Yaketunis Yogyakarta.This study used a qualitative method with descriptive analysis approach. The results of this study found that the strategy of guidance and counseling services for students with visual impairments Yaketunis MTs Yogyakarta includes four service components with each strategy in it as follows: first, basic services with the guidance of a classical strategy, service orientation, information services, group counseling, and data collection . Second, responsive service uses a strategy of individual counseling, group counseling, referrals, collaboration with subject teachers or homeroom, collaboration with parents, consulting, case conferences, and home visits (home visit). Ketigaperencanaan individual using placement services and distribution strategies. Fourth, the support system using network development strategy (networking), activity management, as well as research and development, and evaluation. There is a strategy which is not under the collaboration with stakeholders outside the madrassa, guidance peers (peer guidance) and hand over the case (referral). There is a quirk in guidance and counseling services for students with visual impairments, namely the verbal and non-verbal communication, media usage BK, and career guidance through coaching skills.Keywords: Strategy guidance and counseling services, blind students